Religious Pluralism in Tafsir Muqaran: A Comparative Study of al-Tabari Jami al-Bayan and Quraish Shihab Tafsir al-Misbah - Reza Pahlevi; Hasan Bakti Nasution (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2026)
This article discusses the value of religious pluralism through a comparative analysis of the interpretations of Abu Ja‘far al-Tabarī in Jāmi’ al-Bayān and M. Quraish Shihab in Tafsir al-Misbāh regarding Quranic surah al-Hujurāt [49]: 13. This study employs a qualitative approach using content analysis, focusing on exegetical texts as primary sources and academic literature as secondary sources. The results of the analysis indicate that both exegetes affirm the equality of human origins, recognition of diversity, and piety as the primary measure of nobility. Differences in interpretive styles are evident in al-Tabarī’s textual, hadith-based focus, whereas Quraish Shihab develops contextual meanings in accordance with the realities of contemporary pluralistic society. The implications of this study affirm that the Quran, Surah al-Hujurāt [49]: 13, can serve as an ethical foundation for building tolerant, just, and harmonious interfaith relations without blurring the distinct principles of each religion’s beliefs, while simultaneously strengthening the discourse on Islamic multiculturalism.